2022
DOI: 10.14814/phy2.15229
|View full text |Cite
|
Sign up to set email alerts
|

Carrying a passenger and relaxation before driving: Classification of young drivers’ physiological activation

Abstract: The Organization for Economic Co-operation and Development (OECD) noted that young people under the age of 25 years represent about 10% of the population in OECD countries, but account for more than 25% of drivers killed on the road (OECD, 2006), indicating the importance to focus on this population with regard

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…In the same vein, it can be assumed that the presence of a passenger may lead to increased stress and thus reduced driving performance. 28 However, we cannot make any assumptions about the risky role of passenger presence, which is similar to the finding of the study conducted by Orsi et al They concluded that young drivers, carrying passengers, were particularly vulnerable in single-vehicle collisions; yet, for adult drivers, this collision was more harmful if the driver was alone in the vehicle, 16 which is in line with the results regarding the relationship between lightning status and collision type. The studies assessing rear-end crash exposure methodology revealed that daytime was attributed to many rear-end collisions.…”
Section: Discussionsupporting
confidence: 86%
“…In the same vein, it can be assumed that the presence of a passenger may lead to increased stress and thus reduced driving performance. 28 However, we cannot make any assumptions about the risky role of passenger presence, which is similar to the finding of the study conducted by Orsi et al They concluded that young drivers, carrying passengers, were particularly vulnerable in single-vehicle collisions; yet, for adult drivers, this collision was more harmful if the driver was alone in the vehicle, 16 which is in line with the results regarding the relationship between lightning status and collision type. The studies assessing rear-end crash exposure methodology revealed that daytime was attributed to many rear-end collisions.…”
Section: Discussionsupporting
confidence: 86%
“…The presence of passengers may reduce attention to the driving task and exert direct or indirect psychological pressure to drive on less safe roads. In the same vein, it can be assumed that the presence of a passenger may lead to increased stress and, thus, reduced driving performance [ 20 ]. In addition, pedestrians are highly likely to be more vulnerable compared to other road users because they are less protected than the occupants of closed vehicles.…”
Section: Resultsmentioning
confidence: 99%
“…In order to be as close as possible to reality, the physiological signals of drivers corresponding to the four selected risk factors were collected to train machine learning algorithms. Several experiments were designed and carried out to manipulate the selected risk factors in driving simulator experiments [35], [44]. Table 1 summarizes the three user experiences conducted.…”
Section: ) Data Collectionmentioning
confidence: 99%
“…All machine learning models were trained using the same pipeline implemented in Python with the scikit learn framework [45]. The pipeline is described in detail in [35] and [44].…”
Section: ) Training Machine Learning Modelsmentioning
confidence: 99%